Crystal structure and functional characterization of a light-driven chloride pump having an NTQ motif - Kuglae Kim (Nature Portfolio, 2016)
The atypical rhodopsin ClR from flavobacterium Nonlabens marinusis a light-driven chloride-pumping protein. Here, the authors show that ClR crystal structure presents two chloride ion-binding sites, proposing a molecular pathway for ion transport by this light-driven pump.